Answer: 73
Step-by-step explanation:
Let
a = spoon
b = wand
c = witch
Therefore;
( a + b + c ) + ( a + b + c) + ( a + b + c) = 45 ------------ equation 1
a + a + a = 21 ---------- equation 2
b + (b +b) + b = 12 -------- equation 3
Unknown
b + ( c × ( a+a) = ? .---------equation 4
Solutions
From equation 1
3a = 21
a = 7
From equation 2
4b = 12
b = 3
From equation 3
( 7 + 3 + c ) + ( 7 + 3 + c ) + ( 7 + 3 + c)
= 45
10 + c + 10 + c + 10 + c = 45
30 + 3c = 45
3c = 15
c = 5
From equation 4
3 + ( 5 × (14) )
= 73